2018
DOI: 10.15302/j-fem-2018056
|View full text |Cite
|
Sign up to set email alerts
|

Exploring adoption of augmented reality smart glasses: Applications in the medical industry

Abstract: This study explores the use of augmented reality smart glasses (ARSGs) by physicians and their adoption of these products in the Turkish medical industry. Google Glass was used as a demonstrative example for the introduction of ARSGs. We proposed an exploratory model based on the technology acceptance model by Davis. Exogenous factors in the model were defined by performing semi-structured in-depth interviews, along with the use of an expert panel in addition to the technology adoption literature. The framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…When articles on AR practices used in surgical sciences were examined, it was observed that the highest number of publications was on the domain of General Surgery as clinical domain [13,17,20,44]. And when the key words of the publications were analyzed, it is being observed by Graph 5 that the most frequently used key word was "Augmented Reality" [5,7,8,9,11,13,14,15,16,17,19,20,21,22,23,26,27,29,31,33,34,35,37,38,39,41,42,44,45,46], and the second one was "Virtual Reality" [ 8,9,13,14,16,25,27,37,41]. 1 [34] 1 [37] 1 [20] 1 [24] 1 [35] 1…”
Section: Resultsmentioning
confidence: 99%
“…When articles on AR practices used in surgical sciences were examined, it was observed that the highest number of publications was on the domain of General Surgery as clinical domain [13,17,20,44]. And when the key words of the publications were analyzed, it is being observed by Graph 5 that the most frequently used key word was "Augmented Reality" [5,7,8,9,11,13,14,15,16,17,19,20,21,22,23,26,27,29,31,33,34,35,37,38,39,41,42,44,45,46], and the second one was "Virtual Reality" [ 8,9,13,14,16,25,27,37,41]. 1 [34] 1 [37] 1 [20] 1 [24] 1 [35] 1…”
Section: Resultsmentioning
confidence: 99%
“…Digital technologies have been revolutionizing several industrial sectors, starting from the manufacturing sector to the development of novel products [1,2]. Advancements in Information and Communication Technologies are supporting policymaking and increasing the overall operation efficiency [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Visual acuity, contrast sensitivity, visual field testing, and color tests often reveal complications of the prolonged usage of smart glasses [14]. Before and after using smart glasses, users' visual acuity, contrast sensitivity, visual field parameters, and color distinction abilities show significant differences, indicating serious negative implications of the usage of smart glasses over a prolonged period [4,12,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The usability and feasibility of smart glasses in education and health care areas, such as reading health data, telemonitoring, video recording, documentation, and education, have been extensively examined. 7 , 8 Google Glass, in particular, has been widely adopted in surgical operations, and previous reviews have identified its applicability as a videography device, monitoring device, and navigation display. 9 , 10 Smart glasses adapted to medical settings have been used to offer a first-person point-of-view, mostly in motionless environments such as surgical settings.…”
Section: Introductionmentioning
confidence: 99%